Fe–Al isomorphous and self-pillared ZSM-5 nanosheet catalyst for cracking of n-heptane with enhanced selectivity of light olefins. (June 2022) - Xia, Song; Zhu, Yulin; Tian, Yajie; He, Xinyu; Guo, Longhui; Qiao, Congzhen; Liu, Guozhu
Abstract: Series Fe–Al isomorphous and self–pillared ZSM–5 nanosheets zeolite (Al–Fe–SPZ) with different Fe/Al molar ratios were synthesized by one–pot strategy for catalytic cracking of n –heptane to produce light olefins. All the Al–Fe–SPZ catalysts gave high surface areas and pore volumes, ascribing to the intersection of nanosheet layers. The addition of Fe in zeolite framework resulted in the decrease of surface acid concentrations (especially the strong acid concentrations). The effect of Fe modification on olefins selectivity in catalytic cracking reaction had two sides. On one hand, reducing the amount of acid, helped to inhibit the hydride transfer, cyclization and aromatic cyclization of olefins in the product at adjacent Brønsted acid sites. However, the reduced acid concentrations led to the decrease of the cracking depth, and the cracking of intermediate products (C4 and C5 ) was inhibited, thus giving a decreased olefin selectivity. With Si/(Al+Fe) molar ratio of 100 and Al/Fe ratio of 84/16, Al–Fe–SPZ catalyst gave the highest yield of light olefins (44.8 wt% of ethylene and propylene) in cracking of n –heptane. In addition, Fe modified zeolite catalyst show excellent cracking stability with low coke deposition. Graphical abstract: Image 1 Highlights: Al–Fe-SPZ gave high S BET and V total owing to the intersection of nanosheet layers. Introduction of framework Fe in SPZ reduced acidities especially Brønsted acids. Moderate substitute Al by Fe enhance the olefins yield by Lewis acids. Certain amount of Brønsted acids is required to crack the intermediates product. High catalytic stability is realized by restricted deep dehydrogenation.